The importance of the EMERALD sites for the conservation of biodiversity - Elena Moșanu; Anatol Tariță; Raisa Lozan; Maria Sandu (Acta et Commentationes Exact and Natural Sciences, 2023)
Biodiversity illustrates the extraordinary variety of life on Earth, but technological progress and the intensive use of natural resources have considerably increased the anthropogenic impact on biological diversity. Therefore, to stop the decline of biodiversity through the long-term conservation of the most valuable and endangered species and habitats of European interest to identify, maintain, and restore areas of special interest for the conservation of wild fauna and flora species, the EMERALD Network was established. To integrate the objectives of conservation and protection of species and habitats of national and local interest, education, information, and public involvement in the efficient management of the heritage of the Emerald Network site and Natura 2000, it is necessary to develop management plans for EMERALD sites.